FRI0034 Suppression of hdac5 expression by inflammatory cytokines is required to promote cxcl chemokine production in ra fls. (23rd January 2014) - Angiolilli, C.; Grabiec, A. M.; Tak, P. P.; Baeten, D. L.; Reedquist, K. A.
Abstract : Background: Histone deacetylases (HDACs) are important regulators of gene expression and protein function in the immune system. HDAC inhibitors (HDACi) display anti-inflammatory properties in animal and in vitro models of rheumatoid arthritis (RA), as well as initial safety and efficacy in the treatment of systemic onset juvenile idiopathic arthritis 1 2 . However, as most of the currently available HDACi display little selectivity or specificity for class I (HDAC 1-3, 8) and class II (HDAC 4-6, 9, 10) HDACs, the role of specific HDACs in RA is unclear. Objectives: We examined the relationship between HDAC expression and inflammation in RA synovial tissue and fibroblast-like synoviocytes (FLS). Methods: RNA was isolated from arthroscopic synovial biopsies from 19 RA patients. MMP-1, TNFα, IL-6, and HDAC 1-10 expression was measured by quantitative PCR (qPCR). RA FLS were stimulated with IL-1β, TNFα and LPS and HDAC expression was measured by qPCR. RA FLS were transduced with adenovirus encoding control GFP or GFP-HDAC5, or transfected with control siRNA or siRNA targeting HDAC5. Effects of HDAC5 modulation on RA FLS gene expression were analyzed by custom qPCR array. Results: Positive correlations were observed between RA synovial tissue expression of TNFα and HDAC1 (R=0.651, P=0.003) HDAC2 (R=0.523, P=0.022) and HDAC3 (R=0.570, P=0.011) and between MMP-1 and HDAC1 (R=0.501, P=0.029) and HDAC2 (R=0.512, P= 0.025). A significant negative correlation was observed between synovial tissue expression HDAC5 and IL-6 (R=-0.477, P= 0.039), as well as HDAC5 and clinical parameters of disease activity (CRP: R=-0.664, P= 0.007; ESR: R=-0.556, P=0.013: DAS28: R=-0.567, P=0.011). HDAC5 mRNA expression was significantly and selectively reduced after RA FLS stimulation with TNFα and IL-1β, but not LPS. Of 84 genes regulated in RA FLS by IL-1β or TNFα, mRNA expression of CXCL9, CXCL10, and CXCL11, as well as CXCL10 protein, were selectively upregulated following silencing of HDAC5 expression. Conversely, mRNA expression of these chemokines was suppressed by overexpression of HDAC5 in RA FLS. Conclusions: RA synovial expression of HDAC 1 and 2, but not class II HDACs, positively correlates with local inflammatory mediators, while HDAC5 expression negatively correlates with IL-6 mRNA expression and with disease activity. HDAC5 mRNA is decreased after inflammatory stimulation, and silencing of HDAC5 leads to an increase of CXCL chemokine expression in RA FLS, an effect reversed by HDAC5 overexpression. Our results suggest a protective role for HDAC5 in RA, and that HDACi which fail to target HDAC5 may be more promising for therapeutic applications. References: Joosten, L. A., F. Leoni, S. Meghji, and P. Mascagni. 2011. Inhibition of HDAC Activity by ITF2357 Ameliorates Joint Inflammation and Prevents Cartilage and Bone Destruction in Experimental Arthritis. Mol. Med. 17: 391-396. Vojinovic J, Damjanov N, D'Urzo C, et al. Safety and efficacy of an oral histone deacetylase inhibitor in systemic-onset juvenile idiopathic arthritis. Arthritis Rheum 2011;63:1452–8. [CrossRef][Medline][Web of Science] Acknowledgements: Department of Pharmacology University of California, Davis Disclosure of Interest: None Declared